Extraterritoriality of Hate Speech in Cyberspace from The Perspective of Jurisdictional Limits of The Electronic Information and Transaction Law - Rivana Rivana; Agus Mulyawan; Rizki Setyobowo Sangalang; Heriamariaty Heriamariaty (Jurnal Daulat Hukum, 2026)
The advancement of information and communication technology has created a new sphere of interaction known as cyberspace, where information can be disseminated without geographical boundaries. This condition not only facilitates the exchange of information but also gives rise to complex legal challenges, particularly concerning hate speech offenses. In Indonesia, the regulation of online hate speech is stipulated in Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law) as amended by Law Number 19 of 2016. The problem arises when perpetrators of hate speech reside outside Indonesia, yet their actions have legal impacts within the country. This situation relates to the application of the principle of extraterritoriality as regulated in Article 2 of the ITE Law, which extends Indonesia’s jurisdiction to acts committed abroad that have legal consequences domestically. However, the application of this principle raises debate due to its potential conflict with the principle of territoriality in Indonesian criminal law as regulated in the Criminal Code (KUHP). This study aims to analyze the criminal law regulation of extraterritoriality within the ITE Law regarding hate speech in cyberspace and to examine the limits of Indonesia’s jurisdiction in enforcing the law against cross-border cyber offenses. The research employs a normative legal method with statutory and conceptual approaches. The findings are expected to provide insight into the extent to which the principle of extraterritoriality in the ITE Law can be effectively applied in harmony with the general principles of Indonesian criminal law.